Relationship between stress and bruxism among university students: a cross-sectional study - de Oliveira, Dhelfeson Douglas; Brum-Júnior, Jadimar; Soares, Luana; Cerqueira, Wyllerson; Costa, Igor; Oliveira, Evandro; Gomes, Gabriela; Murta, Agnes; Tavano, Karine Taís; Galvão, Endi; Gonçalves, Patricia; Dumont Flecha , Olga (Revista Estomatología, 2021)
Background: Bruxism is defined as repetitive masticatory muscle activity characterized by clenching or grinding of the teeth and it has been related to psychological factors, such as personality traits, anxiety and stress.Objective: To investigate association between stress and bruxism among university students.Materials and methods: Lipp's Stress Symptoms Inventory for Adults (LSSI) was applied to 253 university students in Diamantina, Brazil. They were clinically evaluated to verify dental wear. The non-instrumental evaluation of probable bruxism was determined by the patients’ reports. Sociodemographic variables and self-reported stress data were collected by using the questionnaire. The chi-square test was used, and significance level of 5% (p